Conservation Agriculture Practices and Their Impact on Soil Health and Pest Dynamics - Vikas Singh; Lalita Kumar Mohanty; Ashoka, P; P. A. Ramsem; Chandan Kumar Panigrahi; Shobha Thakur; Bhim Singh; Vandana Shukla; Ram Gopal; Ram Ashish (Archives of Current Research International, 2025)
Conservation agriculture (CA) practices, including reduced tillage, crop residue retention, and crop rotation, have gained prominence as sustainable farming methods. This review explores the impact of these practices on soil health parameters such as organic matter (OM) content, nutrient availability, water retention capacity, and microbial diversity. Additionally, the article examines how CA practices influence pest dynamics, including weed, insect, and pathogen populations. The complex interactions between soil health and pest pressure under CA systems are discussed. The review highlights the potential of CA to improve soil quality while presenting challenges in pest management that require integrated approaches. Future research directions to optimize CA practices for enhanced soil health and sustainable pest management are suggested.